2006 Florida Plant Disease Management Guide: Sweet Basil - Shouan Zhang; Pamela D. Roberts (EDIS, 2009)
Revised! PP-113, a 2-page fact sheet by Shoan Zhang and Pamela D. Roberts, describes the symptoms and cultural controls for four plant diseases common to Sweet Basil in Florida — downy mildew, leaf spot, bacterial leaf spot, and fusarium wilt. Published by the UF Department of Plant Pathology, March 2009.